Empowering farmers through kombucha production: Enhancing knowledge and economy in Ponggok Village - Juwita, Ratna; Aprilia, Ajeng Rachma; Karury, Anindyah Sutra; Firdaus, Muhammad; Suharti, Suharti; Manggara, Algafari Bakti (Community Empowerment, 2025)
Star fruit is a major commodity in Ponggok Village, Blitar Regency, East Java. However, a significant portion of the harvest is not optimally utilized and often goes to waste. To address this issue, processing star fruit into kombucha offers a promising solution to create new employment opportunities and improve the economic well-being of the community. This community service program was designed to provide the Lumpang Sewu Farmers Group with comprehensive knowledge on the benefits of star fruit, processing techniques, and the production process of star fruit kombucha. The program was implemented in three stages: preparation, execution, and evaluation. The results of the program were highly successful. Post-training, 100% of the participants were able to recognize kombucha as an innovative, value-added product derived from star fruit. Prior to the intervention, 80% of participants primarily used star fruit as fresh fruit. After the training, all participants demonstrated the potential to process star fruit into higher-value products like kombucha. This success is expected to create new economic opportunities and enhance the competitiveness of star fruit-based health products in the market.